2020
DOI: 10.1088/1361-6463/abbf1a
|View full text |Cite
|
Sign up to set email alerts
|

Guided plasma jets directed onto wet surfaces: angular dependence and control

Abstract: The optimal use of atmospheric pressure plasma jets (APPJs) for treatment of surfaces—inorganic, organic and liquid—depends on being able to control the flow of plasma-generated reactive species onto the surface. The typical APPJ is a rare gas mixture (RGM) flowed through a tube to which voltage is applied, producing an RGM plasma plume that extends into the ambient air. The RGM plasma plume is guided by a surrounding shroud of air due to the higher electric field required for an ionization wave (IW) to propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
7
22
0
Order By: Relevance
“…The split can be observed with ε r ⩾ 9, and the split is more pronounced as ε r increases from 9 to 56. The increase in ε r leads to an increase in the electric field between the IW and surface, which has been confirmed through the numerical works [22,39]. The enhanced field led to the split of IW.…”
Section: The Effect Of the Target Relative Permittivitysupporting
confidence: 53%
See 3 more Smart Citations
“…The split can be observed with ε r ⩾ 9, and the split is more pronounced as ε r increases from 9 to 56. The increase in ε r leads to an increase in the electric field between the IW and surface, which has been confirmed through the numerical works [22,39]. The enhanced field led to the split of IW.…”
Section: The Effect Of the Target Relative Permittivitysupporting
confidence: 53%
“…When the IW ejects from the nozzle with small α, the IW rapidly split towards the surface at a few mm above the surface. Previous studies have shown that the gas flow field can be affected by the angle of the gas injection [16,22], the helium flow preferentially flows along the surface in the direction of the angled jet. This can result in changes in the propagation of the IW and thus the deviation value is increased.…”
Section: The Effect Of Appjs Discharge Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Without the restrictions imposed by vacuum systems, atmospheric pressure plasma jets can generate a plasma generally extending a few centimeters from the end of the device. [1,2] The produced plasma in air ambient is also called a plasma plume, [3][4][5][6] in which there are abundant active species. [7] Due to its flexibility and low cost, plasma jet has become a promising tool for the applications in biomedicine, [8,9] material synthesis, [10][11][12] surface modification, [13][14][15] light source, [16] and water purification.…”
Section: Introductionmentioning
confidence: 99%